Are there sufficient prey and protected areas in Nepal to sustain an increasing tiger population?. Issue 1 (2nd January 2016) - Aryal, A.; Lamsal, R.P.; Ji, W.; Raubenheimer, D.
Abstract : Tigers are a globally endangered species that encounter conflict with humans throughout their distribution range. The government of Nepal recently announced in a survey report that the tiger population has increased by 63% (from 121 in 2009 to 198), and aims by 2022 to reach a population size of 250 tigers. Here we analyse the requirement for prey and the size of protected area needed to sustain the projected increased tiger population. The results suggest that the prey biomass and size of current protected areas are insufficient to maintain 250 tigers within the current protected area systems. Therefore, further programmes should be implemented to increase prey populations and increase the area of protected tiger habitat. As Nepal is a pioneer in community-based participatory conservation practices in Asia, a strong, integrated monitoring system in protected parks, a buffer zone and a national forest should be established. Otherwise, an increasing tiger population will frequently range beyond the protected areas, resulting in intensified human–tiger conflict.